Lung function trajectory and biomarkers in the Tasmanian Longitudinal Health Study. Issue 3 (13th September 2021) - Bui, Dinh S.; Agusti, Alvar; Walters, Haydn; Lodge, Caroline; Perret, Jennifer L.; Lowe, Adrian; Bowatte, Gayan; Cassim, Raisa; Hamilton, Garun S.; Frith, Peter; James, Alan; Thomas, Paul S.; et al.
Background and objective: Different lung function trajectories through life can lead to COPD in adulthood. This study investigated whether circulating levels of biomarkers can differentiate those with accelerated (AD) from normal decline (ND) trajectories. Methods: The Tasmanian Longitudinal Health Study (TAHS) is a general population study that measured spirometry and followed up participants from ages 7 to 53 years. Based on their forced expiratory volume in 1 s (FEV1 ) trajectories from age 7 to 53 years, this analysis included those with COPD at age 53 years (60 with AD and 94 with ND) and controls (n=720) defined as never-smokers with an average FEV1 trajectory. Circulating levels of selected biomarkers determined at 53 and 45 years of age were compared between trajectories. Results: Results showed that CC16 levels (an anti-inflammatory protein) were lower and C-reactive protein (CRP) (a pro-inflammatory marker) higher in the AD than in the ND trajectory. Higher CC16 levels were associated with a decreased risk of belonging to the AD trajectory (OR=0.79 (0.63–0.98) per unit increase) relative to ND trajectory. Higher CRP levels were associated with an increased risk of belonging to the AD trajectory (OR=1.07, 95% CI: 1.00–1.13, per unit increase). Levels of CC16 (area under the curve (AUC)=0.69, 95% CI: 0.56–0.81, p=0.002), CRP (AUC=0.63, 95% CI: 0.53–0.72, p=0.01) and the combination of both (AUC=0.72, 95% CI: 0.60–0.83, p<0.001) were able to discriminate between the AD and ND trajectories. Other quantified biomarkers (interleukin (IL)-4, IL-5, IL-6, IL-10 and tumour necrosis factor-α (TNF-α)) were not significantly different between AD, ND and controls. Conclusions: Circulating levels of CRP and CC16 measured in late adulthood identify different lung function trajectories (AD versus ND) leading to COPD at age 53 years. In the general population, two circulating biomarkers (CRP and CC16) are associated with different lung function trajectories leading to COPD in adulthood https://bit.ly/3wqWfb3